TERBENTUKKAH LOYALITAS PADA RS XYZ TERUTAMA BAGIAN POLI PENYAKIT DALAM ? - Patrick Abraham Emilio (Prosiding Working Papers Series In Management, 2018)
The development of hospitals in Indonesia is very fast. Hospital growth is caused by the high level of competition. This research especially in the service of internal illness (poly), which caused in increase loyalty the poly patient at the XYZ Hospitals. This research used sample of 250 respondents, which has used services the poly department in XYZ hospital. This research used non probability sampling and Structural Equation Model as the technique of analysis . The results of this research indicated that brand trust  effected to customer satisfaction, but for service quality and price did not effect to customer satisfaction. Beside that the  brand trust towards loyalty also did not have influence to customer satisfaction variables. The service quality and price had influence on loyalty with customer satisfaction as mediation variabel.Keywords : Trust, Service Quality, Price, Costumer Satisfaction, and Brand Loyalty.